P3.425 Potential For Internet-Based Testing to Reach Gay, Bisexual and Other Men Who Have Sex with Men (MSM) in Canada Facing Current Barriers to Testing For HIV and Sexually Transmitted Infections. (13th July 2013) - Gilbert, M; Hottes, T Salway; Trussler, T; Marchand, R; Taylor, D; Fairley, C; Wong, T; Lester, R; Ogilvie, G; Shoveller, J
Abstract : Background: While pilot studies indicate MSM will use internet testing, no known studies have examined the acceptability of internet testing among diverse MSM. We investigated intention to use internet testing for HIV/STIs, perceived benefits, and drawbacks in the 2011 Sex Now online survey of MSM in Canada. Methods: Participants were recruited through websites (76%), organisations (10%), and word-of-mouth (9%). Intention to use was measured through a 5-point Likert scale. We used multivariable logistic regression (comparing likely or very likely vs other options combined) to identify factors associated with intent (spanning socio-demographics, sexual behaviours, healthcare access, and internet use). Results: Among 7938 Canadian participants, 72% intended to use internet testing with little variation across sub-groups. In multivariable analysis, intent to use was significantly higher ( p < 0.05) for: younger age, less formal education, not being 'out' about sexuality, finding sex partners/searching for health information online, greater mobile phone use, faster uptake of new technologies generally, recent unprotected anal sex with a partner of unknown/discordant HIV status, HIV-negative status, no recent HIV/STI test, avoiding or delaying testing because of privacy concerns or difficulty with access, and dissatisfaction with healthcare services in general. Among men intending to use, most common perceived benefits were greater privacy (32%), convenience (24%), immediacy (13%), and not seeing a nurse/doctor (12%). Among men not intending, most common drawbacks were not seeing a nurse/doctor (20%), wanting to talk to a provider in person about results (17%), not wanting online results (18%), and low trust of service (15%). Conclusions: While all groups of Canadian MSM reported high intention to use internet-based testing, intent was higher for men reporting not testing or avoiding/delaying testing. Our study highlights the potential for an internet-based testing programme for HIV and STI under development in BC to reach men facing current barriers to HIV and STI testing.